2008
DOI: 10.1103/physrevb.78.184515
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory of the structure of magnesium-doped helium nanodroplets

Abstract: We have studied the structure of 4 He droplets doped with magnesium atoms using density functional theory.We have found that the solvation properties of this system strongly depend on the size of the 4 He droplet. For small drops, Mg resides in a deep surface state, whereas for large-size drops it is fully solvated but radially delocalized in their interior. We have studied the 3s3p 1 P 1 ← 3s 21 S 0 transition of the dopant, and have compared our results with experimental data from laser-induced fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 52 publications
(121 reference statements)
4
54
0
Order By: Relevance
“…These apparently contradictory findings were reconciled by density functional theory calculations, which show that although Mg becomes fully solvated in sufficiently large helium droplets (>200 helium atoms), the energy lowering delivered by full solvation is relatively modest. 19 As a consequence, Mg is highly delocalized within the helium droplet and therefore has the opportunity to occasionally explore the subsurface region. This dual nature of the Mg atoms, in which they show both interior and near-surface behavior, accounts for the experimental findings.…”
Section: A Surface-to-submersion Transitionmentioning
confidence: 99%
“…These apparently contradictory findings were reconciled by density functional theory calculations, which show that although Mg becomes fully solvated in sufficiently large helium droplets (>200 helium atoms), the energy lowering delivered by full solvation is relatively modest. 19 As a consequence, Mg is highly delocalized within the helium droplet and therefore has the opportunity to occasionally explore the subsurface region. This dual nature of the Mg atoms, in which they show both interior and near-surface behavior, accounts for the experimental findings.…”
Section: A Surface-to-submersion Transitionmentioning
confidence: 99%
“…It makes use of the Franck-Condon principle within a semiclassical approach. It has been adapted and used by several authors to analyze the absorption spectrum of e.g., lithium in solid H 2 [40], and of different atoms in helium clusters [41,42,43,45]. The particular case of Ca atoms we are interested in has been addressed within DF in pure and mixed helium clusters [12,43].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the light mass of this alkaline earth atom and its weak interaction with helium, Mg impurities are found to be very delocalized inside droplets containing several thousand 4 He atoms, 13 as those of interest in recent experiments. 18,19 In the case of 3 He, we have found that Mg is always in the bulk of the 3 He droplet, as determined by previous DFT calculations.…”
Section: Discussionmentioning
confidence: 99%
“…A similar transition from surface to bulk location of Mg was also found within DFT. 13 This paper is organized as follows. In Sec.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation